Hydrogel Raschig Rings: Synthesis, Geometric Studies and Application for Water Removal from Biodiesel - Henrique L. Goncalves; Patricia Fregolente; Maria Regina Wolf Maciel; Leonardo Fregolente (Chemical Engineering Transactions, 2025)
The presence of water in fuels can lead to significant operational challenges, including microbiological growth that results in fuel degradation and sludge formation, corrosion of equipment, increased turbidity, and impaired engine performance. To address these issues, regulatory standards have been established to limit water content in fuels. In this context, copolymeric hydrogels have emerged as effective materials to remove water from fuels due to their hydrophilicity, enabling them to retain moisture both on their surface and within their structure. The technology of hydrogels as desiccant material can be applied in structured or random packed-beds. In this work, poly(acrylamide-co-sodium acrylate) hydrogels in the shape of Raschig rings were produced using an innovative production method. This geometry, characterized by hollow cylinders with similar height and outer diameter, provides a good surface area-to-volume ratio, making it suitable for chemical engineering applications. The height, inner and outer diameter distributions for the Raschig rings were analyzed before and after the swelling process. It was verified that the geometry of the hydrogels does not undergo noticeable changes after the material is swollen and dried. The Raschig rings at different swelling degrees were used as bed random packings for turbidity reduction from biodiesel in continuous biodiesel treatment process. With a residence time of approximately 10 minutes and hydrogel swelling degrees up to 0.80 g water/g hydrogel, no reduction in performance for the removal of emulsified water was noticed. Furthermore, it was demonstrated that the Raschig rings show geometrical stability after removing water from biodiesel.